An Assessment of the Competitive Position of the Emergent Uruguayan Wine Industry: A Preliminary Netnographic Baseline Study - Angelo A. Camillo; Woo Gon Kim (Beverages, 2021)
This study investigates the competitive position of the Uruguayan wine industry and its potential to become a player in the global wine trade. The study adopts an exploratory, holistic, and qualitative research design, applying desk research, cyberethnography, and electronic correspondence with stakeholders. The research, based on the theory of global business competitiveness, aims to determine the opportunities Uruguay’s wine industry could exploit, based on its competencies, to become a player in the worldwide wine business landscape. The results show that Uruguay is a young wine-producing country; however, it has the potential to become a global competitor. Critical factors identified in the study are geographic location, favorable climate, terrain, hydropower and the high density of the hydrographic network, available agricultural land, the available and well-educated workforce, unique land infrastructure, and the newness of the grape varietal (Tannat) being introduced to the world market with promising results. The paper contributes to the body of knowledge of competitive strategy in wine business research and adds to the scarce literature on the Uruguayan wine industry. Finally, it assesses Uruguay’s current positioning of wine production and competitiveness. The results will benefit stakeholders in the Uruguayan wine industry, researchers, and practitioners in the field.